COMMUNITY ORIENTED POLICING AND PREVENTION OF TRANSNATIONAL CRIMES IN RWANDA: A CASE OF RUBAVU DISTRICT - Nzabahimana, Paul; Irechukwu, Eugenia Nkechi (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
The research project was conducted in Rubavu District under the topic of assessment of community oriented policing and homeland security in Rwanda, case study of Rubavu District. The general objectives the contribution of community oriented policing strategies on home Land security in Rubavu District. Specifically, the researcher assessed the to establish the contribution of community partnership on home land security in Rubavu District, to assess the contribution of training on home land security in Rubavu District and to find out the relationship between Decentralize decision making and home land security in Rubavu District. The research project employed a descriptive research design with a mixed approach including qualitative and quantitative with respondents of 100 participants. The analysis was done with IBM SPSS version 21.0. The questionnaire was the primary method of data collection. The results were presented in Tables. The findings demonstrated that males dominated the socio-demographic of respondents from Rubavu District; about age, the majority was in the range of adult’s persons between 36-65 years dominated the age, the majority of respondents was married. About education level of respondents, the majority of respondent has finished secondary school (A2) and. regarding the occupation, the majority is public servants. Regarding community partnership on homeland security in Rubavu District, the findings shown that there is effective collaboration with community night patrol to fight crimes (41%). The communities work with community security committee for problem solving (45%). The citizens of Rubavu District provide willingly, timely information to community security (39%). Furthermore, the population of Rubavu District willingly contributes to ensure homeland safety services in partnership with the private security companies (47%). Regarding community training on home land security in Rubavu, the findings indicated that community security committee willingly contributes to solve problem of security due to the training given (43%) to contribute on homeland security in Rubavu district. Particular training on community policing contribute to prevention of crimes and problem solving (41%), The officers willingly provide the training on engagement of community problem solving (49%) that training contribute to homeland security in Rubavu District and Private security companies contribute in the training of communities on measures of crimes prevention (32%) that training contribute to homeland security in Rubavu District. Regarding relationship between decentralize decision making and home land security in Rubavu District, the findings indicated that District security committee willingly be flexible to make decision when community-policing committee decided (45%). The local community Security Council willingly made decision about community security and approved (37%). Furthermore, the local communities decision about crimes and miss behavior is approved by district security council (36%) and the local community security committee and private security companies reporting suspicious behaviour to district security council(37%). The model summary results indicated that the independent variables explained 85.2 percent of the variation in community oriented policing strategies on home Land security in Rubavu District, as measured by an adjusted R2 of 85.2 percent, while other variables outside the model and the error term explained 4.8 percent. The correlation results indicated that there is high significant correlation between community partnership and community training with Pearson correlation equal to 0.265±0.001. The same way there is a correlation between community partnership and decentralization (decentralize decision-making) (0.513±0.000). There is a positive correlation between community training and decentralize decision-making (0.431±0.000). The researcher found that there was the contribution of community oriented policing strategies on home Land security in Rubavu District. In additional, a research recommended to mobilize more the youth to be involved in Security Council committee. For more enhancing to the Vigilantes to be given basic training on conduct of their operations and information management. Moreover, the local authorities should do the needful and sensitize the people on the need for homeland security if they are to participate in it fully.